Listening Effort Informed Quality of Experience Evaluation - Sun, Pheobe Wenyi; Hines, Andrew (Frontiers in Psychology, 2022)
Perceived quality of experience for speech listening is influenced by cognitive processing andcan affect a listener’s comprehension, engagement and responsiveness. Quality of Experience(QoE) is a paradigm used within the media technology community to assess media quality bylinking quantifiable media parameters to perceived quality. The established QoE framework provides a general definition of QoE, categories of possible quality influencing factors, and an identified QoE formation pathway. These assist researchers to implement experiments and to evaluate perceived quality for any applications. The framework’s QoE formation pathways do not attempt to capture cognitive effort effects and the standard experimental assessments of QoE minimise the influence from cognitive processes. The impact of cognitive processes and how they can be captured within the QoE framework have not been systematically studied by theQoE research community. This article reviews research from the fields of audiology and cognitive science regarding how cognitive processes influence the quality of listening experience. The cognitive listening mechanism theories are compared with the QoE formation mechanism in terms of the quality contributing factors, experience formation pathways, and measures for experience.The review prompts a proposal to extend the QoE framework to integrate mechanisms fromaudiology and cognitive science into the existing QoE framework in order to properly account for cognitive load in speech listening. The article concludes with a discussion regarding how an extended framework could facilitate measurement of QoE in broader and more realistic application scenarios where cognitive effort is a material consideration.